Study on Thermal Power Loss and Transmission Efficiency of Gas Turbine Gearbox - Yuan Guangqian; Hu Yunbo; Li Jinku; Xia Liangyu (Jixie chuandong)
Thermal power loss and transmission efficiency of gearbox is one of the important indexes to evaluate the quality of gear transmission. Based on the meshing parameters of gears， the mathematical expression of thermal power loss in gear meshing is deduced. Considering oil film thickness and friction factor， the relationship between rolling power loss and sliding power loss in gear meshing and the corresponding relationship between them is analyzed， and the influence law of gear parameters on thermal power loss in gear meshing is obtained. The results show that rolling power loss is positively correlated with oil film thickness， while sliding power loss is positively correlated with friction factor. Based on the influence of gear parameters on the thermal power loss of gear meshing， the principle of selecting high efficiency herringbone gear parameters is proposed.